Irreversibility features of a shell-and-tube heat exchanger fitted with novel trapezoidal oblique baffles: Application of a nanofluid with different particle shapes. (July 2021) - Bahiraei, Mehdi; Naseri, Mohammad; Monavari, Ali
Abstract: The influences of nanoparticle shape on the Entropy Generation Rate (EGR) of a boehmite nanofluid in a shell and tube heat exchanger fitted with trapezoidal oblique baffles are investigated. The hot fluid is the nanofluid with five particle shapes (i.e., platelet, cylinder, blade, brick, and oblate spheroid), whereas the cold fluid is selected to be water. The hot fluid streams at the tube-side, while the cold fluid streams at the shell-side. By the elevation of the Reynolds number ( Re ), in the warm fluid, the thermal and frictional entropy productions increase, while the Bejan number reduces. The nanofluid with platelet-shaped nanoparticles results in the greatest frictional EGR and thermal EGR in the hot fluid, pursued by the suspensions with the cylinder-, blade-, brick-, and Os-shaped nanoparticles, respectively. By rising the Reynolds number, in the cold fluid, the thermal EGR reduces, and the frictional EGR increases. The nanofluid with Os-shaped particles shows the highest thermal and frictional entropy productions in the cold fluid. All in all, with considering the whole heat exchanger regarding the second law of thermodynamics, the platelet-shaped particles are the best ones to be utilized in the heat exchanger, resulting in the lowest irreversibility.